(untitled) (Terr@ Plural, 2021)
Recent fieldwork in the state of Mato Grosso made it possible to find new specimens of trilobites, among them: Metacryphaeus australis, Metacryphaeus sp., and a homalonotide. Taphonomically, it was possible to observe that there are two patterns of conservation, one of which is where the specimens are complete, related to a rapid burial event; and another pattern of preservation where paleoenvironmental conditions provided disarticulation after death. These new findings, as well as their taphonomic interpretations, open possibilities to work on biostratigraphic correlations, in addition to paleobiogeographic assessments for trilobites in South America.